Histone deacetylase inhibitors interfere with angiogenesis by decreasing endothelial VEGFR‐2 protein half‐life in part via a VE‐cadherin‐dependent mechanism. Issue 2 (February 2017) - Hrgovic, Igor; Doll, Monika; Pinter, Andreas; Kaufmann, Roland; Kippenberger, Stefan; Meissner, Markus
Abstract: Recent evidence suggests that histone deacetylase inhibitors (HDACi) may mediate part of their antitumor effects by interfering with tumor angiogenesis. As signalling via the vascular endothelial growth factor receptor‐2 (VEGFR‐2) pathway is critical for angiogenic responses during tumor progression, we explored whether established antitumor effects of HDACi are partly mediated through diminished endothelial VEGFR‐2 expression. We therefore examined the potential impact of three different HDACi, trichostatin A (TSA), sodium butyrate (But) and valproic acid (VPA), on VEGFR‐2 protein expression. TSA, VPA and But significantly inhibit VEGFR‐2 protein expression in endothelial cells. Pertinent to these data, VEGFR‐2 protein half‐life is shown to be decreased in response to HDACi. Recently, it could be demonstrated that expression of VE‐cadherin influences VEGFR‐2 protein half‐life. In our experiments, VEGFR‐2 downregulation was accompanied by HDACi‐induced VE‐cadherin suppression. Interestingly, siRNA‐mediated knockdown of VE‐cadherin led to a pronounced loss of VEGFR‐2 expression on the protein as well as on the mRNA level, implicating that VE‐cadherin not only influences VEGFR‐2 protein half‐life but also the transcriptional level. To further distinguish which of the eight different histone deacetylases are responsible for the regulation of VEGFR‐2 expression, specific HDAC genes were silenced by transfecting respective siRNAs. These studies revealed that HDACs 1, 4, 5 and 6 are preferentially involved in VEGFR‐2 expression. Therefore, these results provide an explanation for the anti‐angiogenic action of HDAC inhibitors via a VE‐cadherin, HDAC 1 and HDACs 4–6‐mediated suppression of VEGFR‐2 expression and might be of importance in the development of new anti‐angiogenic drugs.